Lanthanide cerium(III) complex with deep-red emission beyond 700 nm - Jiayin Zheng; Haodi Niu; Ruoyao Guo; Huanyu Liu; Yujia Li; Wen Lu; Tianming Zhong; Zuqiang Bian; Zhiwei Liu (Nature Communications)
Abstract Luminescent cerium(III) compounds with 5d-4f transition have received extensive interest in phosphor, photocatalysis, and electroluminescence. Due to the high vacuum 5 d energy level, Ce(III) compounds with emission from ultraviolet to yellow region have been well developed, while orange to deep-red emissions are scarce. In this work, we develop a series of molecular Ce(III) complexes with red to deep-red emission by using S-coordinating dithiobiuret ligands, providing new insights into long-wavelength Ce(III) emitters. The longest emission maxima are extended to 725 nm with a photoluminescence quantum efficiency of 31%. Furthermore, it is found that tuning on the steric hindrance yields both mononuclear and dinuclear Ce(III) complexes with different emission colors, as well as different conversion behaviors between the two structures in toluene solution. This work not only shows the great potential of S-coordinating ligands in achieving deep-red Ce(III) emitters, but also demonstrates interesting coordination chemistry of molecular Ce(III) complexes.